2022
DOI: 10.1038/s41419-022-04536-y
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced lncRNA RBM5-AS1 promotes tumorigenesis via activating Wnt/β-catenin signaling in breast cancer

Abstract: Breast cancer is the most common malignancy among women across the globe. Recent studies have revealed that many long non-coding RNAs (lncRNAs) regulate the Wnt/β-catenin signaling pathway in several types of cancer. Hyperactivation of the Wnt/β-catenin pathway has been extensively presented in breast cancer and is involved in breast cancer progression. However, the underlying molecular mechanism remains elusive. In the current study, we found lncRNA RBM5-AS1 was remarkably upregulated in breast cancer cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…More recently, Li and colleagues have also demonstrated the involvement of hypoxia-induced long non-coding RNA RBM5-AS1 in mediating proliferation, migration, invasion, EMT, and stemness maintenance in breast cancer cells under the control of RUNX family transcription factor 2 (RUNX2). Specifically, the authors demonstrated that enrichment of RBM5-AS1 enhanced Wnt signaling by repressing β-catenin degradation and reinforcing the β-catenin:TCF7L2 transcriptional complex ( Li et al, 2022 ).…”
Section: Wnt Signaling and Breast Cscsmentioning
confidence: 99%
“…More recently, Li and colleagues have also demonstrated the involvement of hypoxia-induced long non-coding RNA RBM5-AS1 in mediating proliferation, migration, invasion, EMT, and stemness maintenance in breast cancer cells under the control of RUNX family transcription factor 2 (RUNX2). Specifically, the authors demonstrated that enrichment of RBM5-AS1 enhanced Wnt signaling by repressing β-catenin degradation and reinforcing the β-catenin:TCF7L2 transcriptional complex ( Li et al, 2022 ).…”
Section: Wnt Signaling and Breast Cscsmentioning
confidence: 99%
“…Our previous studies revealed that downregulated RBM5 promotes the progression of BC by activating the Wnt/β-catenin signaling pathway [9]. Consistent with these findings, RBM5 has been shown to promote apoptosis through the inhibition of Wnt/β-catenin signaling [6,10]. However, the specific mechanism of action has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 80%
“…Hypoxia induces the transcriptional upregulation of lncRNA six-transmembrane epithelial antigen of the prostate 3 (STEAP3)-AS1 expression in colorectal cancer by HIF-1α, which subsequently enhances STEAP3 expression through competitive interaction with YTH N6-methyladenosine RNA binding protein F2 31 . Li et al discovered that RNA binding motif protein 5-AS1 hastened the Wnt/β-catenin signalling pathway through the upregulation of β-catenin to promote the breast cancer process under hypoxic conditions 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that lncRNAs are variably expressed in hypoxic environments 22,31,32 . Our previous research con rmed that hypoxia induces an increase in lncRNA-ZEB1-AS1 and lncRNA-NUTF2P3-001 16,17 ; hence, we next sought to demonstrate whether the variational expression of MANCR was signi cant in hypoxia induction.…”
Section: Hypoxia Induced Overexpression Of Lncrna-mancr Expression In...mentioning
confidence: 99%